2020
DOI: 10.3390/land9010027
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Land Cover Change over a 25-Year Period (1993–2018) in Sri Lanka Using Landsat Time-Series

Abstract: Land use and land cover change (LULCC) are dynamic over time and space due to human and biophysical factors. Accurate and up-to-date LULCC information is a mandatory part of environmental change analysis and natural resource management. In Sri Lanka, there is a significant temporal gap in the existing LULCC information due to the civil war that took place from 1983 to 2009. In order to fill this gap, this study presents a whole-country LULCC map for Sri Lanka over a 25-year period using Landsat time-series ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 60 publications
(89 reference statements)
0
13
0
Order By: Relevance
“…For example, Bright et al [37] analyzed post-fire vegetation recovery using LandTrendr-fitted spectral trajectories of NBR as an indicator variable for its conditions. The NBR and NDVI were found to be the most suitable for interannual vegetation changes in LTS analysis [42]. Similarly, Hislop et al [43] demonstrated that both indices accurately capture wildfire disturbance in pixel-based approaches; however, it was shown that NDVI is not so reliable in southeast Australia for detecting post-fire recovery of sclerophyll forests.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Bright et al [37] analyzed post-fire vegetation recovery using LandTrendr-fitted spectral trajectories of NBR as an indicator variable for its conditions. The NBR and NDVI were found to be the most suitable for interannual vegetation changes in LTS analysis [42]. Similarly, Hislop et al [43] demonstrated that both indices accurately capture wildfire disturbance in pixel-based approaches; however, it was shown that NDVI is not so reliable in southeast Australia for detecting post-fire recovery of sclerophyll forests.…”
Section: Introductionmentioning
confidence: 99%
“…This report is inconsistent with what happened in the Syria conflict (2011 to 2018) significantly changes the LULC from 2010 to 2018 and the conflict influenced local environmental resources [144]. Similarly, the civil war of Sri Lanka (1983 to 2009) and the post-war assessment of LULC change between 1993 and 2018 influenced forest reserves and protected areas of the country [145]. During the war period of Sierra Leones (civil war 1991-2002) caused LULC change of Kono district, forest cover structure and spatial extent was contracted [146].…”
Section: Drivers Of Land Use Land Cover Changementioning
confidence: 84%
“…At present, though some reports state Sri Lanka has 16.5% forest cover [31], no published data support this claim. Recent years have recorded the worst forest cover clearing due to infrastructure development activities in Sri Lanka [32], in addition to illegal logging activities recorded throughout the country, though the country has suspended any form of commercial timber extraction [33]. Considering the intensity of resource and environmental degradation and exploitation occurring in the country, it is essential to assess the ecosystem services for better planning of resource utilization and sustainable development.…”
Section: Introductionmentioning
confidence: 99%